Apolipoprotein E genotyping in Turkish myocardial infarction survivors and healthy controls - (:unkn) unknown (Kluwer Academic Publishers, 1995)
The apolipoprotein (Apo) E gene is known to be polymorphic. Three common alleles determine six phenotypes which can easily be detected by restriction fragment length polymorphism. We performed apo E genotyping in myocardial infarction survivors and healthy controls for the first time in the Turkish population. DNA was amplified by polymerase chain reaction (PCR) and the PCR product was digested with restriction enzymes HhaI to detect apo E2, E3, E4 and with TaqI to detect apo E1. Relative allele frequency for the patient group was found to be 0.91 for E3, 0.07 for E2, 0.02 for E4 and for the control group 0.875 for E3, 0.067 for E2, 0.058 for E4. © 1995 National Science Council.
Keywords: HhaI; Polymerase chain reaction; TaqI